2006
DOI: 10.1128/aem.02600-05
|View full text |Cite
|
Sign up to set email alerts
|

Biotic and Abiotic Factors Influencing In Vitro Growth of Escherichia coli O157:H7 in Ruminant Digestive Contents

Abstract: The gastrointestinal tract (GIT) of ruminants is the main reservoir of enterohemorrhagic Escherichia coli, which is responsible for food-borne infections in humans that can lead to severe kidney disease. Characterization of biotic and abiotic factors that influence the carriage of these pathogens by the ruminant would help in the development of ecological strategies to reduce their survival in the GIT and to decrease the risk of contamination of animal products. We found that growth of E. coli O157:H7 in rumen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 53 publications
1
18
0
1
Order By: Relevance
“…In the intestine of ruminants, the microbial counts in the colon and rectum were higher than the counts at any other location (39). Fecal microbial suspensions used during in in vitro fermentation studies of sheep were shown to have microbial counts representative of the counts in the colon and rectum (7). In addition, the fermentation processes and microbial populations in the rumen differ from those in the hindgut (29), so fecal microbial fermentations may represent hindgut fermentation better than ruminal fermentations.…”
Section: Fig 3 Concentrations Of Nalmentioning
confidence: 99%
“…In the intestine of ruminants, the microbial counts in the colon and rectum were higher than the counts at any other location (39). Fecal microbial suspensions used during in in vitro fermentation studies of sheep were shown to have microbial counts representative of the counts in the colon and rectum (7). In addition, the fermentation processes and microbial populations in the rumen differ from those in the hindgut (29), so fecal microbial fermentations may represent hindgut fermentation better than ruminal fermentations.…”
Section: Fig 3 Concentrations Of Nalmentioning
confidence: 99%
“…al., 2002). It tolerates low pH and has antibiotic activity against E. coli O157:H7 (Ogawa et al, 2001;Chaucheyras-Durand et al, 2006).…”
Section: Lactic Acid Bacteria (Lab)mentioning
confidence: 99%
“…Amylolytic bacteria are effective in inhibiting pathogens. Amylolytic LAB eliminated intestinal Escherichia coli 0157:H7 through competitive attachment of the intestinal epithelium (Jones and Rutter, 1972, Muralidhara et al, 1977, Zhao et al, 1998Ohya et al, 2000;Chaucheyras-Durand et al, 2006) and exhibited antibacterial activity against pathogens such as E. coli, Salmonella typhimurium, Staphylococcus aureus, and…”
Section: Amylolytic Bacteriamentioning
confidence: 99%
“…During the HW diet feeding period, rumen samples were collected once a week from the midventral sac 3 h after the morning feeding. These samples were processed under strictly anaerobic conditions as previously described (13), with minor modifications. Briefly, rumen digesta were collected in O 2 -free N 2 -saturated sterile flasks.…”
Section: Methodsmentioning
confidence: 99%
“…These conditions (temperature, oxygenation, and duration) were chosen to reflect the in vivo conditions for each digestive compartment. For the rumen samples, ground feed (40% hay, 60% wheat) was added (25 mg of mixed ground feed for 5 ml of rumen contents) to mimic a fermentation cycle, as previously described (13). Because probiotics need to be administered daily, they were added to the incubation tubes containing the digestive fluids from animals fed probiotics as previously described (13) to obtain a final concentration close to 3 ϫ 10 5 cells ml Ϫ1 of digestive contents.…”
Section: Vol 76 2010 Fates Of Stec Strains In Ruminant Digestive Comentioning
confidence: 99%